Immune evolution from preneoplasia to invasive lung adenocarcinomas and underlying molecular features - Dejima, Hitoshi; Hu, Xin; Chen, Runzhe; Zhang, Jiexin; Fujimoto, Junya; Parra, Edwin R.; Haymaker, Cara; Hubert, Shawna M.; Duose, Dzifa; Solis, Luisa M.; Su, Dan; Fukuoka, Junya; et al. (Nature communications, 2021)
The mechanism by which anti-cancer immunity shapes early carcinogenesis of lung adenocarcinoma (ADC) is unknown. In this study, we characterize the immune contexture of invasive lung ADC and its precursors by transcriptomic immune profiling, T cell receptor (TCR) sequencing and multiplex immunofluorescence (mIF). Our results demonstrate that anti-tumor immunity evolved as a continuum from lung preneoplasia, to preinvasive ADC, minimally-invasive ADC and frankly invasive lung ADC with a gradually less effective and more intensively regulated immune response including down-regulation of immune-activation pathways, up-regulation of immunosuppressive pathways, lower infiltration of cytotoxic T cells (CTLs) and anti-tumor helper T cells (Th), higher infiltration of regulatory T cells (Tregs), decreased T cell clonality, and lower frequencies of top T cell clones in later-stages. Driver mutations, chromosomal copy number aberrations (CNAs) and aberrant DNA methylation may collectively impinge host immune responses and facilitate immune evasion, promoting the outgrowth of fit subclones in preneoplasia into dominant clones in invasive ADC. The evolution of immune landscape in lung adenocarcinoma (ADC) is largely unknown. Here the authors use a cohort of resected invasive lung ADC and its precursors and show a gradual increase of immunosuppression and decrease of anti-tumor response associated with specific genomic and epigenetic features.